2017
DOI: 10.1117/12.2254467
|View full text |Cite
|
Sign up to set email alerts
|

White matter fiber-based analysis of T1w/T2w ratio map

Abstract: Purpose To develop, test, evaluate and apply a novel tool for the white matter fiber-based analysis of T1w/T2w ratio maps quantifying myelin content. Background The cerebral white matter in the human brain develops from a mostly non-myelinated state to a nearly fully mature white matter myelination within the first few years of life. High resolution T1w/T2w ratio maps are believed to be effective in quantitatively estimating myelin content on a voxel-wise basis. We propose the use of a fiber-tract-based anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…We hypothesized that subjects at risk of developing AD would show negatively affected ratio values in regions matching the ones observed in diffusion imaging taking T1w/T2w ratios as indirect measures of myelin content. T1w/T2w ratio has been extensively used in previous research as a non-quantitative descriptor of cortical myelination, but rarely in WM studies (Chen et al, 2017). Results from this present study show significant decreases of this ratio in APOE -ε4 carriers in extended regions of the WM in a cognitively normal population.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that subjects at risk of developing AD would show negatively affected ratio values in regions matching the ones observed in diffusion imaging taking T1w/T2w ratios as indirect measures of myelin content. T1w/T2w ratio has been extensively used in previous research as a non-quantitative descriptor of cortical myelination, but rarely in WM studies (Chen et al, 2017). Results from this present study show significant decreases of this ratio in APOE -ε4 carriers in extended regions of the WM in a cognitively normal population.…”
Section: Discussionmentioning
confidence: 99%
“…Myelin is present in the cortex, but it is most abundant in the cerebral white matter (Shafee et al 2015 ), and the ratio of T1-weighted/T2-weighted (T1w/T2w) MRI images has been suggested as a reliable and straightforward in vivo method to map myelin in the cerebral cortex (Glasser and Van Essen, 2011 ). Some studies have even applied T1w/T2w to white matter tracts in the neonatal (Lee et al 2015 ; Chen et al 2017 ) and adult brain (Colmenares et al 2021 ). However, upon comparison with other myelin mapping imaging modalities, including Myelin Water Fraction (MWF), T1w/T2w ‘may be not an optimal index of subcortical myelin content’ (Arshad et al 2017 ), and its use as a myelin marker has been criticized (Uddin et al 2018 , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, Voxel Based Morphometry (VBM) style analyses are never appropriate in T1w/T2w studies of the cerebral cortex. Skeletonized methods such as Tract-Based-Spatial-Statistics (TBSS; Smith et al, 2006) offer the best option for voxelwise white matter analysis (e.g., Operto et al, 2019), though tractography-based tract analyses would likely be even better (Chen et al, 2017; Thompson et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, however, it is NOT appropriate to attempt "VBMstyle" analyses of these T1w/T2w ratio volumes in lieu of proper surface-based cortical analyses for reasons described elsewhere (Glasser et al, 2016b;Coalson et al, 2018), and also because partial volume effects of CSF, grey matter, and white matter will completely dominate the differential effects of myelin content in traditional volume-based analyses (i.e., the differences in T1w/T2w ratio between tissues are much larger than those within tissues). Skeletonized methods such as Tract-Based-Spatial-Statistics (TBSS; Smith et al, 2006) offer the best option for voxelwise white matter analysis (e.g., Operto et al, 2019), though tractography-based tract analyses would likely be even better (Chen et al, 2017;Thompson et al, 2020).…”
Section: Correction Of T1w/t2w Ratio Volumesmentioning
confidence: 99%